Novel control implementation for electric vehicles based on fuzzy-back stepping approach - M Sellali.; A. Betka; S. Drid; A. Djerdir; L. Allaoui; M. Tiar (Energy, 2019)
The present paper deals with a real-time assessment of a fuzzy –backstepping based control applied to a battery-supercapacitor (SC) hybrid energy storage system (HESS). To properly emulate the behavior of an electric vehicle, the proposed topology is extended to a PMSM drive, that represents the traction part. The proposed control scheme is divided into two parts: The first part plans a fuzzy logic power management approach, to operate the system in a smart way: First, It ensures an optimal load power-sharing, focusing the operation of the involved sources in a safe mode. Second, a quite regulation of both the dc bus and the SC voltage without additional controllers. The second part proposes a back-stepping direct torque control (BS-DTC), associated to a space vector modulation (SVM) strategy, to ensure decoupled torque and flux control of the PMSM machine. The experimental results, conducted on a small …